The Complement System Is Essential for the Phagocytosis of Mesenchymal Stromal Cells by Monocytes - Gavin, Caroline; Meinke, Stephan; Heldring, Nina; Heck, Kathleen Anne; Achour, Adnane; Iacobaeus, Ellen; Höglund, Petter; Le Blanc, Katarina; Kadri, Nadir (Frontiers in Immunology, 2019)
Mesenchymal stromal cell (MSC) therapy is a promising tool in the treatment of chronic inflammatory diseases. This has been ascribed to the capacity of MSC to release a large variety of immune-modulatory factors. However, all aspects of the mode of therapeutic MSC action in different diseases remain unresolved, mainly because most of the infused MSC are undetectable in the circulation within hours after infusion. The aim of this study was to elucidate the fate of MSC after contact with plasma. We found that upon contact with blood, complement proteins including C3b/iC3b are deposited on MSC. . Importantly, we also found that complement bound to MSC enhanced their phagocytosis by classical and intermediate monocytes via a mechanism that involves C3 but not C5. Thus, we describe for the first time a mechanism which might explain, at least partly, why MSC are not found in the blood circulation after infusion. Our results indicate that MSC immune-modulatory effects could be mediated by monocytes that have phagocytosed them.